Pelatihan Ovitrap Untuk Pengendalian DBD Di Kota Semarang - Martini Martini; M. Sakundarno Adi; Nissa Kusariana; Ari Udiyono; Muh Fauzi (Poltekkes Kemenkes Surakarta, 2025)
Background: Dengue hemorrhagic fever (DHF) is a significant and growing global public health challenge in subtropical regions, affecting millions of people worldwide. Ovitrap is an innovation aimed at effectively controlling mosquito populations and reducing the risk of diseases like DHF. The ovitrap training aims to enhance public understanding of dengue vector control and to develop skills in effectively using ovitraps to prevent the spread of disease. Methods: The activity began with an explanation and determination of the schedule in collaboration with partners. The implementation included a pre-test, the delivery of materials on mosquito vector control and ovitrap techniques, demonstrations, participant practice, and was concluded with a post-test to evaluate understanding. Results: The increase in the average knowledge score of participants from 7.86 to 9.00 after the activity was supported by the results of the Wilcoxon Signed-Rank test with a significance value (p-value) of 0.006 (p<0.05) which means there is a significant difference between the average knowledge before and after the activity. Conclusion: The training on ovitrap techniques for DHF control succeeded in improving the community's understanding and skills in managing the risk of DHF disease spread. The community is advised to routinely use ovitraps to control mosquito populations and be accompanied by maintaining environmental hygiene.